The Penn Effect and transition: The new EU member states in international perspective - Richard Frensch; Achim Schmillen (Osteuropa-Institut Regensburg, 2011)
Recent panel studies have found relatively high point estimates for the elasticity of ag-gregate price measures with respect to productivity in (former) transition economies, while other studies report price-productivity elasticity estimates to depend positively on average productivity in the sample. We aim to reconcile both results by putting com-parative price developments of transition economies in an international perspective. We argue that estimating simple price-productivity relationships without the inclusion of other real factors connected to reform effort might severely bias estimates for CEEC economies. Our results imply that, when controlling for reform effort and therefore avoiding this endogeneity problem, the price-productivity-elasticity for CEEC econo-mies was not different from that of non-transition economies during the first 15 years of transition.
Keywords: F40; F43; 330; Balassa-Samuelson; transition; Preisniveau; Produktivität; Kaufkraftparität; Balassa-Samuelson Effekt; Schätzung; Übergangswirtschaft; EU-Staaten (Osteuropa)